Digitizing the Map of Agricultural Plantation Areas in a Southern Region of Miri for Sustainable Agricultural Land Use Planning - Ngoi, Erik Yiew Tuang (Curtin University, 2021)
Massive agricultural land use expansion shows the need for sustainable agricultural land use planning in the Kabuloh region of Miri. Agricultural land use planning is vital to minimize the negative impacts caused by agricultural development. Hence, the suitability and the potential impact of existing agricultural activities in the Kabuloh region were assessed in the environmental and socio-economic aspects. A sustainable agricultural land use map was digitized for future planning in the study location.